Formulation and evaluation of potash alum as deodorant lotion and after shaving astringent as cream and gel - Alzomor, Abdulkarim K.; Moharram, Ahmad Safe; Al Absi, Nahlah Mansour (International Current Pharmaceutical Journal, 2014)
Potash alum has different traditional application including deodorant and astringent. In order to wide advancement in development of pharmaceutical and cosmetic industries we preferred to work in this field as well as for improvement of safety and efficacy of traditionally used natural products. The aim of the present study was to formulate deodorant potash alum as lotion dosage form and astringent as cream and gel dosage forms. The activity of potash alum against axillaries normal microbiota was tested in vitro using wells diffusion agar method for different concentrations (0.1% to 9%) on Mueller Hinton (MH) agar and the minimum inhibitory concentration (MIC) was determined as 2% and also subculture was done to determine the activity of potash alum as bacteriostatic. Alum powder has wide traditional usage as astringent to prevent bleeding from minor cuts and for its accelerated healing. Therefore, a more appropriate dosage form was designed in a suitable concentration (2% gel) to elongate its astringent activity by its higher retention time due to highly viscous nature of gel. Using suitable excipients, 2% lotion and gel were prepared by dispersion method while emulsification was used for preparation of the potash alum cream of same strength. The above formulations were evaluated by comparing their pH, viscosity, spreadability, contents uniformity and in vitro diffusion. The stability study was carried out at 25°C for 3 months and at 40°C with 75±5% RH for one month. pH, viscosity, spreadability, extrudability and consistency of the products were evaluated at the end of the studies. The results indicated no change in the formulations demonstrating their stable nature as a dosage form and suitability as a commercial product line. DOI: http://dx.doi.org/10.3329/icpj.v3i2.17512 International Current Pharmaceutical Journal, January 2014, 3(2): 228-233